Neonatal C1 to C2 Osteomyelitis Leading to Instability and Neurological Decline. Issue 4 (June 2015) - Glotzbecker, Michael P.; Wasser, Aubrey M.; Troy, Michael J.; Proctor, Mark; Emans, John B.
<x xml:space="preserve">Abstract</x> Background: Vertebral osteomyelitis of the upper cervical spine requiring surgical treatment in children is rare. Surgical treatment of the immature spine is commonly associated with certain risks and complications. We describe a unique treatment approach for a young child that required emergent stabilization of the upper cervical spine due to progressive instability caused by osteomyelitis. Methods: A 3-month-old infant with neurological decline from progressive instability of the occiput C1 and C2 was admitted for surgical treatment after failed bracing. The patient had reduction and occiput to C2 posterior fusion and segmental instrumentation, with nonsegmental instrumentation extending in the soft tissues from C2 to T4 with the intent of providing stabilization without fusion and permitting further growth. Results: The implants were removed 1 year after the original procedure. At 2 years following implant removal, he continued to have mild global developmental delay but was progressing well and was able to navigate independently with a posterior walker, using AFOs for support. Subaxial cervical motion and x-ray appearance were normal. Conclusions: The technique used here to overcome the difficulty of providing secure immobilization of the craniocervical junction while not creating inadvertent fusion of the subaxial cervical spine may have application in other clinical situations. Level of Evidence: Level V.